PUBLIC TRANSPORTATION SERVICE PERFORMANCE ASSESSMENT APPLICATION FOR BUS RAPID TRANSIT(BRT) TRANS SEMARANG - Abdayani, Maharani Putri; Siswanto, Joko; Lestari, Astri (Jurnal Ilmiah Teknologi dan Rekayasa, 2025)
Analysis of service performance through surveys distributing questionnaires to BRT passengers is a complicated process which results in it being less effective and efficient due to using many devices and human resources. A BRT service performance assessment application using the Importance Performance Analysis (IPA) method is proposed to solve this problem which is built using the waterfall method (analysis, design, coding and testing). The public transport service performance assessment application can produce analysis and cartesian diagrams for assessing the performance and importance of BRT services automatically and in real time. The application was tested using black box testing on 7 test cases for admins and 5 test cases for respondents with valid results or in line with expectations. The application is used to analyze service performance in Corridor 4 BRT Trans Semarang which is filled directly by 100 passengers (respondents) with the results of quadrant I of the Cartesian diagram about drivers who are orderly in traffic and prioritize safety (statement 5), and buses have safety equipment (statement 6) can be prioritized in service. BRT Trans Semarang managers can use the resulting application to improve the effectiveness and efficiency of service performance analysis, identify service aspects that need to be prioritized, and support data-based decision making for public transportation (BRT) management.